Case report: Atypical Parkinsonism following SARS-CoV-2 infection - Polverino, Paola; De Santis, Tiziana; Perdixi, Elena; Chiò, Adriano; Albanese, Alberto (Frontiers in Neurology, 2023)
A wide range of neurological manifestations have been reported during Covid-19 pandemic, including a variety of parkinsonian cases. The association of numerous viruses with the development of persistent or transient parkinsonism has been well-documented. We observed a patient who developed a levodopa non-responsive parkinsonian syndrome with dysautonomia during a prolonged stay at home for Covid-19. Although the temporal proximity of the emerging parkinsonian features with a Covid-19 diagnosis suggested a causal relationship, we considered the possibility of a coincidental occurrence of multiple system atrophy. We discuss the patient’s clinical features in relation to established clinical diagnostic criteria and review differential diagnoses as well as the role of SARS-CoV-2 infection.